Occupational Health Problems: An Assessment of the Cardiovascular Health Status of Road Construction Workers in Imo State, Nigeria - Bwala, John Mark; Amadi, Agwu Nkwa; Iwuala, Chimezie Christian; Enebeli, Ugo Uwadiako (European Scientific Journal, ESJ, 2025)
Occupational health problems among road construction workers are a significant concern due to the hazardous nature of their work. Known to be uniquely demanding and highly stressful, road construction work has been linked to cardiovascular problems. This study assessed the cardiovascular health status of road construction workers in Imo State, Nigeria. Using a cross-sectional descriptive design, data were collected from 353 road construction workers through structured questionnaires and physical assessments, including blood pressure (BP) and pulse rate (PR) measurements. The findings revealed that all the road construction workers were males, 82 (23.2%) had systolic hypertension, 35 (9.9%) had diastolic hypertension, and 22 (6.2%) had tachycardia (elevated PR). However, 269(76.2%) did not have regular medical check-ups. Thus, a significant proportion of road construction workers had poor cardiovascular health status; however, they lacked access to regular medical check-ups and occupational health services. These findings underscore the urgent need for health education, workplace health promotion, and policy-driven interventions that aim at mitigating occupational risks and promoting cardiovascular health among construction workers. The study recommends routine health screening and implementation of wellness programs to enhance workers’ well-being. Addressing these occupational health challenges is crucial for improving productivity and safeguarding the health of road construction workers in Imo State and similar settings.